Pengendalian Kebisingan Dari Aktivitas Penerbangan di Lingkungan Sekitar Bandara Sultan Thaha Jambi dengan Pemanfaatan Ruang Terbuka Hijau - Nur Sodiq; G M Saragih; Peppy Herawati (Universitas Batanghari Jambi, 2021)
Noise is a sound pollution and its existence is undesirable in a certain level and time, which has the potential to cause human health problems and environmental comfort. One of the causes of noise levels is due to airport operational activities, from landing to take off. For this reason, it is necessary to control the noise around the Sultan Thaha Jambi airport area, by utilizing green open space as a barrier that can reduce noise levels. This study aims to determine the level of airport noise in certain zones and evaluate the existence of green open space (RTH) whether it is appropriate to become a natural barrier as a barrier to reduce noise caused by flight activities from Sultan Thaha Jambi airport. The results showed the noise level dB (A) from flight activities in each zone, namely the lowest in zones 1 and 3, amounting to 52.08 dB (A), and the highest in zone 5 at 87.93 dB (A). , while the existence of Green Open Space (RTH) is only in zone 1, and 3 are forest park areas, and fields around the Sultan Thaha Jambi airport area, so the existence of this Green Open Space (RTH) is able to reduce noise levels by 2.11 dB (A) based on KEP-48 / MNLH / 11/1996 the quality standard of the allowable noise level is 50 dB (A). While zone 5 is a residential area, the noise level figure is quite high, namely 87.93 dB (A), due to the densely populated area, lack of green open space (RTH), and proximity to motorized vehicle transportation activities, and adjacent to the runway. runway airport. However, not all activities are carried out continuously. So that the residential area is still feasible if exposed to noise exposure either from airport activities or other activities.